Inserción de Colombia en las relaciones internacionales; en el contexto de la segunda postguerra mundial. (2010)
Finished the Second World War some diplomatic and political situations were modified in the international area. United States was standing out in America; promoted to create regional organizations to stop any threat come from the exterior . In this context; it wanted to analyze the role of Colombia in the international policy and in the diplomatic matters during the consolidation of the new world order.